Analisis Penerapan Penggunaan Aplikasi Coretax pada Pemerintah Kabupaten Sukabumi - Annisa Rahmawati; Romli Romli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Indonesian government continues to promote the modernization of tax administration through digital systems, one of which is the Core Tax Administration System (Coretax). This system is expected to enhance efficiency, transparency, and tax compliance, including within the public sector. This study aims to analyze the implementation of the Coretax application in the administration and reporting of Monthly Tax Returns (SPT Masa) by regional government expenditure treasurers in the Sukabumi Regency Government, as well as to identify the challenges encountered during its implementation.This research adopts a qualitative approach using field studies and literature reviews. Data were collected through in-depth interviews with expenditure treasurers from several Regional Government Work Units (SKPD) and through document analysis related to tax reporting. Data analysis was conducted descriptively, referring to the Technology Acceptance Model (TAM) and the Slippery Slope Framework to examine user perceptions, system utilization, and implications for tax reporting compliance.The findings indicate that the implementation of Coretax in the Sukabumi Regency Government has not yet been fully optimized. Several challenges were identified, including system access disruptions, application instability, limited user understanding, and insufficient technical socialization and assistance. These issues have led to delays in Monthly Tax Return reporting, discrepancies in tax data, and obstacles in financial disbursement processes and revenue-sharing fund distribution. Nevertheless, Coretax demonstrates significant potential to support orderly tax administration if accompanied by system improvements and strengthened human resource capacity.The study concludes that the successful implementation of Coretax is influenced not only by technological aspects but also by user readiness, organizational support, and continuous assistance strategies. The results of this study are expected to provide valuable input for local governments and the Directorate General of Taxes in improving the implementation of Coretax within the public sector.